Study on Thermal Unstable Vibration of Rotor under Journal Whirl with Large Amplitude in Journal Bearing - Qilong Hu; Min Zhu; Jiangang Yang (International Journal of Rotating Machinery)
To investigate the thermal unstable vibration caused by journal whirls with large amplitude in journal bearing, an analysis model of lubricant film thickness is established. The journal surface temperature distribution is solved, and the reason for journal surface temperature difference appearance and its influence on rotor vibration are analyzed. Taking a turbogenerator as an example, the journal surface temperature difference and the induced rotor thermal bending under synchronous whirl in the bearing are calculated. Meanwhile, an engineering vibration fault with its treatment is presented. Results show that, the journal surface circumferential temperature difference is caused by viscous shearing within lubricant film under journal whirls with large amplitude in journal bearing. The direction of temperature difference is related to the direction of unbalanced force acting on journal. The temperature difference causes rotor thermal bending, which can be converted to a thermal unbalance on the rotor. The rotor vibration is caused by both thermal and initial unbalance. When the rotor is running below or at the critical speed, the vibration is on the increase until it leads to instability of the rotor eventually. When the rotor is running above the critical speed, the rotor vibration fluctuates periodically. Reducing the initial (mechanical) unbalances decreases the rotor vibration and the journal surface circumferential temperature difference.